(untitled) (Nóema, 2013)
The Course on The Hermeneutic of the Subject problematizes a theme that goes through the whole Foucault’s thought, that of technique. The article, through a dialogue among Foucault, Heidegger and Simondon, aims to trace the development of this theme, also asking the way the technique works when related to processes of subjection and subjectification.